2022
DOI: 10.3389/fimmu.2022.886374
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of the role of necroptotic damage-associated molecular patterns in tissue fibrosis

Abstract: Fibrosis is defined as the abnormal and excessive deposition of extracellular matrix (ECM) components, which leads to tissue or organ dysfunction and failure. However, the pathological mechanisms underlying fibrosis remain unclear. The inflammatory response induced by tissue injury is closely associated with tissue fibrosis. Recently, an increasing number of studies have linked necroptosis to inflammation and fibrosis. Necroptosis is a type of preprogrammed death caused by death receptors, interferons, Toll-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 178 publications
0
4
0
Order By: Relevance
“…Immune infiltration and immune checkpoint analyses performed on the three datasets indicated that TNFRSF1A is a good diagnostic marker of OS. Necroptosis is preprogrammed death triggered by death receptors, interferons, toll-like receptors, intracellular RNA and DNA sensors, and other mediators [42]. Based on univariate Cox regression analysis, among the 14 evaluated NRGs [22], the prioritization of TN-FRSF1A arises from its noteworthy association with OS prognosis and its pertinence in immune-related mechanisms in OS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Immune infiltration and immune checkpoint analyses performed on the three datasets indicated that TNFRSF1A is a good diagnostic marker of OS. Necroptosis is preprogrammed death triggered by death receptors, interferons, toll-like receptors, intracellular RNA and DNA sensors, and other mediators [42]. Based on univariate Cox regression analysis, among the 14 evaluated NRGs [22], the prioritization of TN-FRSF1A arises from its noteworthy association with OS prognosis and its pertinence in immune-related mechanisms in OS pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cell injury and death are common events in inflammatory diseases, such us UC and CD, but they have been only recently recognized as drivers of fibrosis. For instance, an increasing number of studies have linked necroptosis (a form of programmed necrosis) to inflammation and fibrosis in renal, liver, heart or lung fibrosis ( Liu et al, 2022 ). Cell products released by cells undergoing necrosis (passive, programmed, or after apoptosis) are called damage-associated molecular patterns (DAMPs), that can directly activate profibrotic responses of immune cells or nonimmune cells (epithelial cells, endothelial cells, and fibroblasts) triggering fibrosis ( Liu et al, 2022 ).…”
Section: Other Roles Of Epithelial Cells In Intestinal Fibrosis: Less...mentioning
confidence: 99%
“…For instance, an increasing number of studies have linked necroptosis (a form of programmed necrosis) to inflammation and fibrosis in renal, liver, heart or lung fibrosis ( Liu et al, 2022 ). Cell products released by cells undergoing necrosis (passive, programmed, or after apoptosis) are called damage-associated molecular patterns (DAMPs), that can directly activate profibrotic responses of immune cells or nonimmune cells (epithelial cells, endothelial cells, and fibroblasts) triggering fibrosis ( Liu et al, 2022 ). In addition, epithelial cells contain a myriad of intracellular substances normally not recognized by the immune system but, during cell necrosis, they are passively released in the surrounding microenvironment and trigger inflammation.…”
Section: Other Roles Of Epithelial Cells In Intestinal Fibrosis: Less...mentioning
confidence: 99%
See 1 more Smart Citation